2015
DOI: 10.1111/ssqu.12149
|View full text |Cite
|
Sign up to set email alerts
|

A Tale of “Two Souths”: White Voting Behavior in Contemporary Southern Elections*

Abstract: Objective We empirically demonstrate that the long‐held political distinction between the Deep South and the Peripheral South persists to this day. Methods Data from the Cooperative Congressional Election Study (CCES) are employed in logistic regression models to assess differences in the likelihood of voting Republican among Deep and Peripheral South whites in gubernatorial, senatorial, and presidential contests. Additionally, recent data on the partisan and racial composition of various elective offices docu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…A body of studies suggested that marital status was not a significant predictor of political attitudes or political participation (Banerjee & Ray Chaudhuri, 2018;Berinsky & Lenz, 2011;Schussman & Soule, 2005 and never married are more likely to support more conservative right-wing party compared with married participants, controlling for the effects of age and sex (Werts et al, 2013). Contrasting findings, however, showed that married people were more likely to support Republicans than Democrats relative to unmarried people in congressional elections in the United States (McKee & Springer, 2015). Denver (2008) argued that married citizens tend to adhere to more traditional values, which relate to higher conformity to the idea of 'good citizenship.'…”
Section: Discussionmentioning
confidence: 94%
“…A body of studies suggested that marital status was not a significant predictor of political attitudes or political participation (Banerjee & Ray Chaudhuri, 2018;Berinsky & Lenz, 2011;Schussman & Soule, 2005 and never married are more likely to support more conservative right-wing party compared with married participants, controlling for the effects of age and sex (Werts et al, 2013). Contrasting findings, however, showed that married people were more likely to support Republicans than Democrats relative to unmarried people in congressional elections in the United States (McKee & Springer, 2015). Denver (2008) argued that married citizens tend to adhere to more traditional values, which relate to higher conformity to the idea of 'good citizenship.'…”
Section: Discussionmentioning
confidence: 94%
“…Put plainly, the black takeover of the Democratic Party has caused white Mississippians to control public affairs by comprising an almost lily‐white Republican majority (Hood, Kidd, and Morris, ). As is true throughout the South (Black, ; McKee, ) and especially in the Deep South (McKee and Springer, ), the political clout of black Mississippians has approached a new nadir in the post‐VRA era because whites have overwhelmingly realigned to the GOP and no longer need Democratic votes to implement their preferred policies. Under these conditions, black votes matter if they can affect the outcome of Republican contests, since the GOP nominee is practically assured election against the Democratic opponent in the general election—an opponent who is increasingly likely to be African American (see Hayes and McKee, ) because blacks now constitute the majority of Democratic supporters in most southern states…”
Section: Resultsmentioning
confidence: 99%
“…Democrats are now in the minority in both chambers, African Americans comprise 60 percent or more of the Democratic senate and house delegations, and an all‐white Republican Party rules the legislature. In short, after enjoying a brief partnership in a majority Democratic coalition, black political influence in Mississippi has reached a new low, a condition now common throughout the Deep South (McKee and Springer, ). It is within this political context that black votes would become critical to the political survival of embattled Republican Thad Cochran as he sought a seventh term in the U.S. Senate.…”
Section: The Rise and Fall Of Black Influence In Mississippi Politicsmentioning
confidence: 99%
“…McKee further examines vote choice in the 2006 U.S. House elections and finds that a Deep South dummy variable is a statistically significant predictor of vote choice above and beyond other relevant explanatory variables. In a further analysis McKee and Springer () find that whites in the Deep South were also significantly more likely to vote Republican for other political offices, again even after accounting for other explanatory variables that might affect vote choice.…”
Section: The “Two Souths” Controversymentioning
confidence: 93%